Evaluation of the AllType kit for HLA typing using the Ion Torrent S5 XL platform. (23rd October 2019) - Cargou, Marine; Ralazamahaleo, Mamy; Blouin, Laura; Top, Isabelle; Elsermans, Vincent; Andreani, Marco; Guidicelli, Gwendaline; Visentin, Jonathan
Abstract : HLA genotyping by next‐generation sequencing is now widely performed. We aimed at evaluating the performance of the One Lambda AllType kit using Thermo Fisher Scientific reagents on the Ion S5 XL platform. Reads were analyzed using the TypeStream Visual software. We performed 15 runs between April and September 2018 to type DNA at the HLA‐A/B/C/DRB1/3/4/5/DQA1/DQB1/DPA1/DPB1 loci from 340 samples and 15 positive controls. We observed only seven (0.1%) critical mistakes among the 6009 alleles typed, corresponding to two allele dropouts, one false heterozygous typing assignment, and four phasing abnormalities. Among the 1793 presumably new alleles detected by the analysis software, 11 displayed exon mismatches, of which nine were confirmed as new alleles and two had been described previously. Intron mismatches were observed among the remaining presumably new alleles, of which 371 were considered as probably new, and 1411 were rejected for at least one sequence feature such as homopolymers (n = 1206), nucleotide doublet repeats (n = 26), low read depth (<200 reads, n = 93), high background (>20%, n = 79), or phasing abnormalities (n = 7). A comparison of the AllType results with those obtained using other methods at the second‐field resolution level showed 99.5% (1497/1504) concordance for the HLA‐A/B/C/DRB1/DQB1/DPB1 loci. Similar agreement was observed between the HLA‐C or HLA‐DRB3/4/5 results and common linkage disequilibrium, with 96.6% (657/680) and 97.2% (530/545) concordance, respectively. Therefore, the AllType kit used with the Ion S5 XL platform displayed satisfactory performance for HLA typing in current clinical practice.